Economic Considerations on Nutrient Utilization in Wastewater Management - Josef Maroušek; Anna Maroušková (Energies, 2021)
There is wide consensus that Spirulina can serve as a tool for wastewater management and simultaneously provide feedstock for biorefining. However, the economic aspects associated with its use remain a significant challenge. Spirulina cultivated in wastewater decreased the concentrations of both ammonia and nitrate and also served as a biodiesel source. The oil obtained in the feedstock was subjected to transesterification and turned into biodiesel. The biodiesel was subsequently analyzed in a test motor (water-cooled, four-stroke, single-cylinder compression ignition with injection). The tests were conducted at a constant 1500 rpm, and the output power was 3.7 kW. Mixtures of diesel and biodiesel were also enriched with carbon nanotubes (CNTs). The amount of CNTs added to the diesel was 30 mg L−1. The algae and de-oiled biomass were characterized using XRD analysis, and an ultrasonicator was used to mix the CNTs with diesel and spirulina blends. A series of tests were conducted at different load conditions (25%, 50%, 75%, and 100%) for all fuel blends. Test results were compared with a neat diesel engine with a CR of 17.5:1. Among the fuel blends, the B25 reported improved brake thermal efficiency and reduced emissions. The outcomes are a reduction in thermal efficiency of 0.98% and exhaust gas temperature of 1.7%. The addition of Spirulina biodiesel blends had a positive impact on the reduction of greenhouse gas emissions, including reductions of 16.3%, 3.6%, 6.8%, and 12.35% of CO, NOx, and smoke, respectively. The specific fuel consumption and CO2 emissions were reduced by 5.2% and 2.8%, respectively, for B25 fuel blends compared to plain diesel and B50. Concerning cost competitiveness, vigorous research on microalgae for the production of biodiesel can cut production costs in the future.